2018
DOI: 10.1590/0102-33062018abb0115
|View full text |Cite
|
Sign up to set email alerts
|

Floral resins of Philodendron adamantinum (Araceae): secretion, release and synchrony with pollinators

Abstract: Philodendron is the only genus of Araceae in which resin release occurs in the inflorescence. The resinous secretion adheres to the smooth body surface of the pollinating scarab beetles and allows attachment of pollen grains, making its transport possible. In order to understand the process of resin synthesis and release to the external environment, we used structural, ultrastructural and histochemical analyses at different stages of development of the inflorescences of Philodendron adamantinum. Two types of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 43 publications
1
11
0
Order By: Relevance
“…Notably, the resin ducts of Alismataceae are narrow and lack a sheath (this study), as observed in the ducts of Clusiaceae [29,44]. Sheaths formed by two cell layers surrounding the duct occur in Anacardiaceae [45], Hypericaceae [46], and Araceae [47]. Narrow secretory ducts are not common in angiosperms, but they have also been reported in Philodendron adamantinum Mart.…”
Section: Resin Duct Structuresupporting
confidence: 58%
See 2 more Smart Citations
“…Notably, the resin ducts of Alismataceae are narrow and lack a sheath (this study), as observed in the ducts of Clusiaceae [29,44]. Sheaths formed by two cell layers surrounding the duct occur in Anacardiaceae [45], Hypericaceae [46], and Araceae [47]. Narrow secretory ducts are not common in angiosperms, but they have also been reported in Philodendron adamantinum Mart.…”
Section: Resin Duct Structuresupporting
confidence: 58%
“…Narrow secretory ducts are not common in angiosperms, but they have also been reported in Philodendron adamantinum Mart. ex Schott (Araceae) [47] and Hypericum perforatum L. (Hypericaceae) [46].…”
Section: Resin Duct Structurementioning
confidence: 99%
See 1 more Smart Citation
“…This lack of structural studies of secretory activity has resulted in considerable controversy about the presence of floral nectaries or even true nectar secretion in this genus (see Hartley et al, 2017). The occurrence of secretory activity in Araceae inflorescences has been documented for some species, but only in rare studies has a structural analysis identified the origin of the secretory product (Skubatz and Kunkel, 1999; Hadacek and Weber, 2002; Gonçalves‐Souza et al, 2017, 2018). Our study demonstrated the existence of active tepalar nectaries in Anthurium andraeanum .…”
Section: Discussionmentioning
confidence: 99%
“…In some Philodendron, the cyclocephaline scarabs were also observed to lick the abundant exudates from receptive stigmas (Gottsberger et al 2013). In general, fertile staminate and pistillate flowers are not heavily damaged by the feeding activity, even during the male phase when temporarily resident cyclocephaline scarabs eat copious amounts of pollen (Gibernau et al 1999;Gottsberger et al 2013;Pereira et al 2014;Maldonado et al 2015; but see Gonçalves-Souza et al 2018 for an exception). This feeding preference is explained by lower quantities of calcium oxalate crystals (e.g.…”
Section: Introductionmentioning
confidence: 99%